FETAL GROWTH RESTRICTION IN PORPHYROMONAS GINGIVALIS-INFECTED PREGNANT RATS: RESTRI KSI PERTUMBUHAN JANIN PADA TIKUS HAMIL YANG DIINFEKSI PORPHYROMONAS GINGIVALIS - Banun Kusumawardani; Marsetyawan Soesatyo; Djaswadi Dasuki; Widya Asmara (Dentika: Dental Journal, 2011)
The periodontopathogens Porphyromonas gingivalis may directly or indirectly attack the fetus by releasing toxins into the blood stream that could reach the placental and influence fetal development . This study aimed to determine the effect of periodontal infection with P. gingivalis on fetal development in pregnant rat model. Female rats were infected with live-P. gingivalis at concentration of 109colony forming unit/ml into subgingival sulcus before and/or during pregnancy. Group I: without P. gingivalis infection ; group II: P. gingivalis infection before and during pregnancy; group III: P. gingivalisinfection before pregnancy; and group IV: P. gingivalis infection during pregnancy. They were sacrified on gestational day 14 and 20. Fetuses were evaluated for weight and crown-tail length. The results showed that the dams infected with P.gingivalis significantly decrease the mean of fetal weights, lengths and placental weights compared with the control group (p<0.05). The percentages of fetal growth restriction at the time of sacrifice were 6.66, 100, 72.97 and 87.09% growthrestricted fetuses in group I, II, III, and IV, respectively. When weights of growth- restricted fetuses of the treated groups were compared with the control group there were significant differences (p<0.05). P. gingivalis was detected by API ZYM system in the blood of umbillical cord from the treated groups. In conclusion, in pregnant rat models, periodontal infection with P. gingivalis affects fetal development. The maternal P. gingivalis infection on periodontal tissue can result in P. gingivalis dissemination to umbillical cord and induction of FGR.